The paradox of screening: Rural women's views on screening for postnatal depression - Small Rhonda E; Armstrong Susan J (BMC, 2010)
Abstract Background Universal screening for postnatal depression is currently being promoted in Australia to assist detection and treatment of affected women, yet debate continues internationally about the effectiveness of screening. One rural shire in Victoria has been screening all women for postnatal depression at maternal and child health checks for many years. This paper explores the views of women affected by this intervention. Methods A postal survey was sent to an entire one year cohort of women resident in the shire and eligible for this program [n = 230]. Women were asked whether they recalled having been screened for postnatal depression and what their experience had been, including any referrals made as a result of screening. Women interested in providing additional information were invited to give a phone number for further contact. Twenty women were interviewed in-depth about their experiences. The interview sample was selected to include both depressed and non-depressed women living in town and on rural properties, who represented the range of circumstances of women living in the shire. Results The return rate for the postal survey was 62% [n = 147/230]. Eighty-seven women indicated that they were interested in further contact, 80 of whom were able to be reached by telephone and 20 were interviewed in-depth. Women had diverse views and experiences of screening. The EPDS proved to be a barrier for some women, and a facilitator for others, in accessing support and referrals. The mediating factor appeared to be a trusting relationship with the nurse able to communicate her concern for the woman and offer support and referrals if required. Conclusions Detection of maternal depression requires more than administration of a screening tool at a single time point. While this approach did work for some women, for others it actually made appropriate care and support more difficult. Rather, trained and empathic healthcare providers working in a coordinated primary care service should provide multiple and flexible opportunities for women to disclose and discuss their emotional health issues.